2020
DOI: 10.1088/1742-6596/1515/2/022033
|View full text |Cite
|
Sign up to set email alerts
|

Detecting vulnerabilities of information resources of unmanned vehicles method based on dynamic evaluation of Markov sequences properties

Abstract: Related to the development and research of methods for ensuring computer security of unmanned vehicles in the information infrastructure of a smart city approaches are considered. The approaches are based on nonparametric statistics methods for evaluating changes in the information states of controlled UMV resources, which include communication channel, processor, and memory. It is proposed to evaluate the changes for each of these resources in such characteristics as the degree of resource loading and its rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The authors of the article also obtained some results in the works, the solution of problems of intrusion detection in computer networks based on the assessment of changes in the network traffic state using statistical criteria, nonparametric statistics methods [4], multi-agent model of UMV information interaction [5], mechanisms adaptation of artificial immune systems to control the parameters of UMV resources state [6], anomalies detection using Markov sequences [7], and also on the concept development of an intelligent monitoring system for solving large-scale tasks in cloud computing environments [8] The problem of information security is multifaceted, costly and knowledge-intensive. The search for effective solutions to ensure information security leads to the need to create new structural elements in systems and networks.…”
Section: Figure 1: X R Types Of Main Bts Interfacesmentioning
confidence: 99%
“…The authors of the article also obtained some results in the works, the solution of problems of intrusion detection in computer networks based on the assessment of changes in the network traffic state using statistical criteria, nonparametric statistics methods [4], multi-agent model of UMV information interaction [5], mechanisms adaptation of artificial immune systems to control the parameters of UMV resources state [6], anomalies detection using Markov sequences [7], and also on the concept development of an intelligent monitoring system for solving large-scale tasks in cloud computing environments [8] The problem of information security is multifaceted, costly and knowledge-intensive. The search for effective solutions to ensure information security leads to the need to create new structural elements in systems and networks.…”
Section: Figure 1: X R Types Of Main Bts Interfacesmentioning
confidence: 99%
“…Now, ransomware attack is targeting smart-vehicles and smart cities that could result in the loss of human lives and financial instability. Moreover, there have been attempts where researchers have shown that malware is one of the keys and emerging security threats that can be launched by exploiting the wireless communication system of AVs [7], [8]. For instance, by exploiting known vulnerabilities in the design and implementation of onboard communication systems, embedded software, and application software [9]- [11] as sketched in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…The key to the afore-mentioned success of remote attacks on AVs is information sharing by the vehicles over a wireless medium which increases the susceptibility of the vehicles to different security and malware attacks. Consequently, data exchange including input and output data as well as protecting Electronic Control Unit (ECUs) inside the AVs are among the most significant security issues for the intelligent vehicles [8], [17]. Specifically, the most damaging cyber threats, are emerging as the vehicles connect to the Internet, provide onboard Wi-Fi hotspot services, communicate with other vehicles and ITS infrastructures, and support advanced applications such as over-the-air (OTA) ECU firmware update [7].…”
Section: Introductionmentioning
confidence: 99%